2022
DOI: 10.15420/cfr.2022.14
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in Older People with Heart Failure: Roles of the Geriatrician and Pharmacist

Abstract: Heart failure (HF) is a common health condition that typically affects older adults. Many people with HF are cared for on an inpatient basis, by non-cardiologists, such as acute medical physicians, geriatricians and other physicians. Treatment options for HF are ever increasing, and adherence to guidelines for prognostic therapy contributes to polypharmacy, which is very familiar to clinicians who care for older people. This article explores the recent trials in both HF with reduced ejection fraction and HF wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 79 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…According to our results, a multidisciplinary approach including experts in frailty, HF, and geriatric pharmacology may be the most effective strategy to manage patients with HF and frailty, and polypharmacy, to reduce the risk of PIM being prescribed, and as a consequence, potentially harmful drug-drug interactions taking place[ 40 ]. In fact, Essa et al recently demonstrated that a multispecialty multidisciplinary intervention reduced hospitalizations due to adverse drug reactions by significantly reducing the anticholinergic burden in patients with HF[ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, a multidisciplinary approach including experts in frailty, HF, and geriatric pharmacology may be the most effective strategy to manage patients with HF and frailty, and polypharmacy, to reduce the risk of PIM being prescribed, and as a consequence, potentially harmful drug-drug interactions taking place[ 40 ]. In fact, Essa et al recently demonstrated that a multispecialty multidisciplinary intervention reduced hospitalizations due to adverse drug reactions by significantly reducing the anticholinergic burden in patients with HF[ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, beta-blockers may be prescribed twice a day, angiotensin-converting enzyme inhibitors once a day and diuretics as needed. Although such complex regimens were proven to be effective collectively, the true benefit of the regimen depends on the patient's adherence [71]. Therefore, when we define polypharmacy, the complexity of regimen also should be accounted for.…”
Section: Regimen Complexitymentioning
confidence: 99%
“…Or, the two medications interact with each other to weaken the clinical benefit of one or worsen the side effect of one. Therefore, when we define polypharmacy to assess its impact on patients, consideration of drug-drug interactions should be accounted for [71].…”
Section: Interaction With Other Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geriatrics are generally characterized by the decline in organ function, such as the kidneys and liver, leading to changes in the pharmacodynamics and pharmacokinetics of the drugs they consume. Additionally, geriatric patients often suffer from cardiovascular diseases such as coronary heart disease, heart failure, hypertension, and stroke, requiring multiple treatment therapies [7,8]. It is estimated that more than 40% of geriatrics aged >65 y use five or more drugs, and at least 12% use ten drugs.…”
Section: Introductionmentioning
confidence: 99%